Redescription of the Indo-West Pacific scorpionfish Scorpaena neglecta Temminck & Schlegel, 1843, a senior synonym of four nominal species (Teleostei: Scorpaenidae) - Wibowo, Kunto; Motomura, Hiroyuki (Zootaxa, 2019)
The Indo-West Pacific scorpionfish Scorpaena neglecta Temminck & Schlegel (1843) is redescribed on the basis of two syntypes and 129 additional specimens from Korea, Japan, Taiwan, Indonesia and Australia, and a lectotype is proposed. Four nominal species, Scorpaena fimbriata Döderlein in Steindachner & Döderlein, 1884, Scorpaena izensis Jordan & Starks, 1904, Scorpaena hemilepidota Fowler, 1938 and Scorpaenopsella armata Fowler, 1938, are regarded as junior synonyms of Scorpaena neglecta. Morphological changes with growth of S. neglecta are discussed.